View-graph construction framework for robust and efficient structure-from-motion. (June 2021) - Cui, Hainan; Shi, Tianxin; Zhang, Jun; Xu, Pengfei; Meng, Yiping; Shen, Shuhan
Highlights: We use an incremental manner to construct view graph, rather than computing the relative geometry in each edge independently. By iteratively performing local reconstruction, the verified maximum spanning tree is extended into our view graph. The relative geometry is estimated by local reconstruction, which has less ambiguity and is more robust than matrix decomposition. By embedding our view graph, both the reconstruction efficiency and robustness are greatly improved. Our view graph has a wide applicability, and in principle it can be inserted into any SfM systems. Abstract: A view-graph is vital for both the accuracy and robustness of structure-from-motion (SfM). Conventional matrix decomposition techniques treat all edges of view-graph equally; hence, many edge outliers are produced in matching pairs with fewer feature matches. To address this problem, we propose an incremental framework for view-graph construction, where the robustness of matched pairs that have a larger number of feature matches is propagated to their connected images. Given pairwise feature matches, a verified maximum spanning tree (VMST) is first constructed; for each edge in the VMST, we perform a local reconstruction and register its visible cameras. Based on the local reconstruction, pairwise relative geometries are computed and some new epipolar edges are produced. In this way, these newly computed edges inherit the robustness and accuracy of VMST, and by embedding them into VMST, our view-graph is constructed. We feed our view-graph into a standard SfM pipeline and compare this newly formed system with many of state-of-the-art SfM methods. The experimental results demonstrate that our view-graph provides a better foundation for conventional SfM systems, and enables them to reconstruct both general and ambiguous images.